ANALYSIS AND IMPLEMENTATION NAÏVE BAYES FOR FAST TRACK STUDENT GRADUATION DIAGNOSIS AT STMIK ROYAL - Andhini Asri Awaliyah Arifin; Arridha Zikra Syah; Akmal Akmal (STMIK Royal, 2022)
Abstract: Student graduation is one thing that needs to be considered because it is included in the College's Internal Quality Assurance Standards (SPMI). STMIK Royal is one of the universities experiencing problems with student graduation. To achieve the quality of these graduates, a graduation diagnosis with the standards that have been set for students who are still carrying out studies is very necessary so that anticipatory steps can be taken from the beginning to overcome the occurrence of graduation problems in the academic field. This research aims to diagnose fast-track student graduation by using a data mining model with a classification function. The technique used for the classification data mining model is the Naïve Bayes Algorithm. The dataset used as training and testing data is data from the 2021 STMIK Royal fast track students. The criteria used to determine student graduation are Gender, class, credits, GPA, Tuition Fee, Guidance Process, and the KKL Report. The results of the classification modeling with the Naïve Bayes Algorithm produce an accuracy value of 83%. Keywords: data mining; graduation; naïve Bayes Abstrak: Kelulusan mahasiswa adalah salah satu hal yang harus diperhatikan karena termasuk ke dalam Standar Penjaminan Mutu Internal (SPMI) perguruan tinggi. STMIK Royal adalah salah satu perguruan tinggi yang mengalami masalah kelulusan mahasiswa. Untuk mencapai kualitas lulusan tersebut, diagnosis kelulusan dengan standar yang telah ditetapkan untuk mahasiswa yang masih menjalankan studi sangat diperlukan sehingga dapat dilakukan langkah antisipasi dari awal untuk menanggulangi terjadinya permasalahan kelulusan dalam bidang akademik. Tujuan diadakannya penelitian ini untuk untuk mendiagnosis kelulusan mahasiswa fast track dengan menggunakan model data mining dengan fungsi klasifikasi. Teknik yang digunakan untuk model data mining klasifikasi adalah Algoritma Naïve Bayes. Dataset yang akan digunakan untuk menjadi data latih dan data uji adalah data mahasiswa fast track STMIK Royal tahun 2021. Kriteria yang digunakan untuk diganosis kelulusan mahasiswa, diantaranya Jenis Kelamin, Kelas, SKS, IPK, Uang Kuliah, Proses Bimbingan, dan Pengumpulan Laporan KKL. Hasil pemodelan klasifikasi dengan Algoritma Naïve Bayes menghasilkan nilai akurasi sebesar 83%. Kata kunci: data mining; kelulusan; naïve bayes